A Cross-Sectional Study Elucidating Associated Predictors in Postpartum Depression among Pakistani Women: Postpartum Depression among Pakistani Women - Shumaila Zulfiqar; Zahra Tariq; Hafsa Adnan; Iram Anjum (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Postpartum depression is a psychological condition that deteriorates a mother’s cognitive health and overall family functioning. This survey-based cross-sectional study was done on postpartum mothers between 15-40 years of age to determine the epidemiology of postpartum depression in Pakistan. Edinburg postnatal depression scale (EPDS) and an adapted relationship assessment tool were used to determine the prevalence of postpartum depression. A total of n=103 responses were collected from different regions of Pakistan. Univariate and Bivariate analyses, Pearson Correlation Tests, and Binary Logistic Regression Analyses were applied to investigate the predictors. Postpartum depression was found in 67.96 % of the participating women and EPDS was found to be the most reliable tool to evaluate postpartum depression.